The contribution of the speeches of Elihu to the argument about suffering in the book of Job a study in narrative continuity - Waters, Larry J. (Lewiston, N.Y [u.a.] Mellen Press, 2009)
Foreword / by Roy B. Zuck -- Introduction -- The purpose of the book of Job -- The authenticity of the Elihu speeches -- Opponents of Elihu's authenticity -- Advocates of Elihu's authenticity -- Conclusions and assumption -- Contributions and limitations -- The state of current literature and the need and relevance of this study -- The procedure and methodology of this study -- The framework for Elihu's view of suffering -- The complexity of the problem of suffering -- The problem of undeserved suffering described -- The problem of undeserved suffering defined -- The genuineness of undeserved suffering as an issue in the book of Job demonstrated -- The labyrinth of explanations for the problem of undeserved suffering documented -- The problem of the paradox of moral order and human tradition versus divine justice -- The problem described -- The concepts of retribution and compensation theology defined and contrasted -- Job's dilemma : a summary -- Outline and examination of the person Elihu -- The context of Elihu speeches -- An outline of Job 32-37 -- The person of Elihu -- Analysis of the Elihu speeches and his view of suffering, part one -- Elihu's first speech (Job 32) : God's wisdom is not limited by human assumption : a defense of Elihu's intrusion -- Elihu's second speech (Job 33) : God is not silent : a defense of God's goodness -- Elihu's third speech (Job 34) : God is not unjust : a defense of God's justice -- Analysis of the Elihu speeches and his view on suffering, part two -- Elihu's fourth speech (Job 35) : God is not uncaring : a defense of God's silence -- Elihu's fifth speech (Job 36-37) : God's use of his power is just and righteous : preparation for the theophany -- Summary of Elihu's view of suffering in chapters -- Elihu's view of suffering compared and contrasted -- Ancient Near Eastern view -- Satan's view -- Eliphaz's view -- Bildad's view -- Zophar's view -- Job's view -- God's view -- Summary and observations -- Summary chart comparing and contrasting all views -- Elihu's view of suffering relating to the theology of God, man, and retribution -- Elihu's view of suffering relative to the theology of God -- Elihu's view of suffering relative to the theology of man -- Elihu's view of suffering relative to retribution theology -- Conclusion -- Summary of chapters and principles relating to suffering -- Significant findings : Elihu's methodology -- Elihu's role in relation to Job -- Elihu's role in relation to the three friends -- Elihu's role in relation to God -- Elihu's role in relation to suffering -- Concluding remarks
Introduction ; The purpose of the book of Job ; The authenticity of the Elihu speeches ; Opponents of Elihu's authenticity ; Advocates of Elihu's authenticity ; Conclusions and assumption ; Contributions and limitations ; The state of current literature and the need and relevance of this study ; The procedure and methodology of this study ; The framework for Elihu's view of suffering ; The complexity of the problem of suffering ; The problem of undeserved suffering described ; The problem of undeserved suffering defined ; The genuineness of undeserved suffering as an issue in the book of Job demonstrated ; The labyrinth of explanations for the problem of undeserved suffering documented ; The problem of the paradox of moral order and human tradition versus divine justice ; The problem described ; The concepts of retribution and compensation theology defined and contrasted ; Job's dilemma : a summary ; Outline and examination of the person Elihu ; The context of Elihu speeches ; An outline of Job 32-37 ; The person of Elihu ; Analysis of the Elihu speeches and his view of suffering, part one ; Elihu's first speech (Job 32) : God's wisdom is not limited by human assumption : a defense of Elihu's intrusion ; Elihu's second speech (Job 33) : God is not silent : a defense of God's goodness ; Elihu's third speech (Job 34) : God is not unjust : a defense of God's justice ; Analysis of the Elihu speeches and his view on suffering, part two ; Elihu's fourth speech (Job 35) : God is not uncaring : a defense of God's silence ; Elihu's fifth speech (Job 36-37) : God's use of his power is just and righteous : preparation for the theophany ; Summary of Elihu's view of suffering in chapters ; Elihu's view of suffering compared and contrasted ; Ancient Near Eastern view ; Satan's view ; Eliphaz's view ; Bildad's view ; Zophar's view ; Job's view ; God's view ; Summary and observations ; Summary chart comparing and contrasting all views ; Elihu's view of suffering relating to the theology of God, man, and retribution ; Elihu's view of suffering relative to the theology of God ; Elihu's view of suffering relative to the theology of man ; Elihu's view of suffering relative to retribution theology ; Conclusion ; Summary of chapters and principles relating to suffering ; Significant findings : Elihu's methodology ; Elihu's role in relation to Job ; Elihu's role in relation to the three friends ; Elihu's role in relation to God ; Elihu's role in relation to suffering ; Concluding remarks.
Includes bibliographical references (p. 273-281) and indexes
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Elihu -- (Biblical figure); Elihu; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc